Validated RP-HPLC Method for the Determination of Zolmitriptan - A Serotonin 5-HT Receptor Agonist - Annapurna, M. Mathrusri; Nanda, Bidyut (Journal of Pharmacy and Nutrition Sciences, 2022)
A simple precise, accurate RP-HPLC method has been developed and validated for analysis of Zolmitriptan (ZLM). The separation and quantization were achieved on a 250 mm reversed phase column with a hydrophilic linkage between silica particles and hydrophobic alkyl chains. The mobile phase was constituted (flow rate 0.8 ml min-1) of eluant A (CH3OH) and eluant B (aqueous tetra butyl ammonium hydrogen sulphate) (pH 3.4; 10 mM) using isocratic elution with UV detection at 224 nm. The method showed good linearity for ZMT in the 1–100 μg mL-1 range with regression equation 15576x ± 99401 and correlation coefficient 0.999 respectively. The limit of quantitation (LOQ) and limit of detection (LOD) were found to be 0.8134 and 0.2687 μg mL-1 respectively. Finally the applicability of the method was validated according to ICH guidelines and can be applicable for the analysis of commercial dosage forms.